2020
DOI: 10.3390/cancers12061440
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of Early and Late Recurrent Pancreatic Ductal Adenocarcinoma Using Patient-Derived Organoid Cultures

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is associated with high mortality and will become the second most common cause of cancer-associated mortality by 2030. The poor prognosis arises from a lack of sensitive biomarkers, limited therapeutic options, and the astonishingly high recurrence rate after surgery of 60–80%. The factors driving this recurrence, however, remain enigmatic. Therefore, we generated patient-derived organoids (PDOs) from early- and late-recurrent PDAC patients. Cellular identity of PDOs was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 57 publications
2
15
0
1
Order By: Relevance
“…Establishment of organoid cultures 14 , 15 and determination of KRAS mutational status 16 was achieved as previously described. For passaging, Matrigel domes with organoids were disrupted from a 24-well plate and collected in 10 mL cold splitting medium.…”
Section: Methodsmentioning
confidence: 99%
“…Establishment of organoid cultures 14 , 15 and determination of KRAS mutational status 16 was achieved as previously described. For passaging, Matrigel domes with organoids were disrupted from a 24-well plate and collected in 10 mL cold splitting medium.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, suppressing glutamine uptake by inhibiting glutamine transporter ASCT2 significantly inhibited prostate cancer growth and metastasis (96). Moreover, in patient-derived organoids model, Braun et al found that glutamine was increased more than four times from early-recurrent PDAC patients with the development of tumor recurrence within the first six months after radical surgery, than those from late-recurrent patients, suggesting that glutamine metabolism may be diverse according to different tumor malignancies (97). To date, the exact mechanisms linking glutamine metabolism to tumor metastasis are still unclear, but studies have demonstrated that glutamine may participate in the metastatic process through the interaction with EMT, tumor immunology and tumor microenvironment.…”
Section: Glutaminolysis and Cancer Metastasis: Emt Tumor Immunologymentioning
confidence: 99%
“…Cervical cancer is the most common gynecological malignancy, which can be primary tumors that derived either from the genitalia or the products of conception, or secondary tumors impacted by other cancerous organs with metastasis [ 12 ]. Metabolism plays a crucial role in the process of tumor initiation, development, and recurrent [ 13 , 14 ]. Metabolic reprogramming was utilized by cancer cells to achieve limited nutrient resources for proliferation, growth, survival, and long-term maintenance when competing with normal cells [ 15 ].…”
Section: Discussionmentioning
confidence: 99%